Clinical characteristics of patients submitted to surgery in a dental clinic of Southern Santa Catarina - de Araujo, Paula Fernanda; Raupp Nunes de Araújo, Viviane; Bisognin Ceretta, Luciane; Netto, Soraia; Crema, Marlowa Marcelino; Simões, Priscyla Waleska; Goulart Azambuja, Fabiano; Ceretta, Renan Antônio (O Mundo da Saúde, 2016)
This study presents the clinical characteristics and systemic disorders of patients seen at a university clinic of oral surgery. Descriptive study that evaluated 304 records of patients undergoing surgical procedures in a clinic of Oral Surgery from 2013 to 2014. Most patients were male (n=154; 50.7%), aged 8 to 78 years, and had some kind of systemic change (n=144; 47.4%). The procedures were performed over the extractions (54.3%, n=165), and removing root remainders (n=165; 55.6%). There were 35 (11.5%) cases of clinical complications and 101 (33.2%) had harmful habits with potential to interfere in the pre, trans and postoperative periods. Systemic disorders were significantly associated with age (p<0.001). It can be concluded that knowledge of the systemic situation is valuable in dentistry, since many diseases can influence prescribing and method of conduct of a particular procedure.